TNFR2 Is a Crucial Hub Controlling Mesenchymal Stem Cell Biological and Functional Properties - Beldi, Ghada; Bahiraii, Sheyda; Lezin, Chloé; Nouri Barkestani, Mahsa; Abdelgawad, Mohamed Essameldin; Uzan, Georges; Naserian, Sina (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cells (MSCs) have drawn lots of attention as gold standard stem cells in fundamental and clinical researches during the last 20 years. Due to their tissue and vascular repair capacities, MSCs have been used to treat a variety of degenerative disorders. Moreover, MSCs are able to modulate immune cells’ functions, particularly T cells while inducing regulatory T cells (iTregs). MSCs are very sensitive to inflammatory signals. Their biological functions could remarkably vary after exposure to different pro-inflammatory cytokines, notably TNFα. In this article, we have explored the importance of TNFR2 expression in a series of MSCs’ biological and functional properties. Thus, MSCs from wild-type (WT) and TNFR2 knockout (TNFR2 KO) mice were isolated and underwent several ex vivo experiments to investigate the biological significance of TNFR2 molecule in MSC main functions. Hampering in TNFR2 signaling resulted in reduced MSC colony-forming units and proliferation rate and diminished the expression of all MSC characteristic markers such as stem cell antigen-1 (Sca1), CD90, CD105, CD44, and CD73. TNFR2 KO-MSCs produced more pro-inflammatory cytokines like TNFα, IFNγ, and IL-6 and less anti-inflammatory mediators such as IL-10, TGFβ, and NO and induced Tregs with less suppressive effect. Furthermore, the TNFR2 blockade remarkably decreased MSC regenerative functions such as wound healing, complex tube formation, and endothelial pro-angiogenic support. Therefore, our results reveal the TNFα–TNFR2 axis as a crucial regulator of MSC immunological and regenerative functions.